Ode to East Texas : The Art of Lee Jamison - Jamison, Lee, 1957- (Book collections on Project MUSE., 2021)
"Having built a solid reputation as a respected Texas Regionalist painter, Lee Jamison became convinced that East Texas, while rich in natural beauty and historic interest, has typically been under-represented as a subject of serious artists. Seeking to remedy this lack of parity, the artist traveled the winding roads and tree-lined passages of East Texas for well over a year, observing, sketching, and journaling along the way. Exhibiting an unshakeable awareness of place and a poet's sensibility, Lee Jamison's Ode to East Texas stands as an affectionate hymn to a familiar region, an invitation to a new appreciation of its qualities"--